Work process in the emergency room of the large hospital: a vision of nursing workers - Karine Pacheco Barbosa; Lucilane Maria Sales da Silva; Marcelo Costa Fernandes; Raimundo Augusto Martins Torres; Rândson Soares de Souza (Rev Rene)
The aim of this article is to know the point of view of the nursing workers about the support structural and the work process developed in the emergency room of a major hospital. This is a qualitative approach descriptive study. The research population was constituted of nurses, technicians and nursing assistants of the emergency room, using a semi-structured interview for the data collection. The information was analysis was made through a technique known as content analysis. We stood out the complaints and concerns of nursing workers about the working process, personal satisfaction, the risks and damages to health, as well as the necessary conditions for the best performance of work in the emergency room identifying that the professionals realize that there are risks of illness and the absence of safety inside the hospital environment, especially in the emergency room. It often makes them feel helpless by the bodies who supervise the workers’ health.